EFFECT OF INCUBATION ON SPERM MOTILITY AND LIVABILITY OF LABRADOR RETRIEVER DOG SPERMATOZOA PRESERVED AT 5ºC IN DIFFERENT EXTENDERS - DAS, A; BISWAS, R K; DEKA, B C (The Indian Journal of Animal Reproduction, 2017)
Four ejaculates from each of two adult Labrador Retriever dogs collected by digital manipulation method were extended @ 1:4 in Tris-Egg Yolk-Citric Acid-Glucose (TEYCAG), Tris-Egg Yolk-Citric Acid-Fructose (TEYCAF) and Egg Yolk-Citrate-Glycine-Glucose (EYCGG) extender by split sample technique. The extended semen samples were preserved at 50C for 24, 48, 72 and 96h. Thereafter, the aliquots of preserved semen samples were incubated at 37oC for 0, 2, 4, 6 and 8h. Irrespective of preservation period and incubation period, the mean sperm motility and live sperm percentage differed (p<0.05) between TEYCAG and EYCGG extenders, and between TEYCAF and EYCGG extenders, but was similar (p>0.05) between TEYCAG and TEYCAF extenders. Mean sperm motility and live sperm percentage were higher (p<0.05) in TEYCAG and TEYCAF extenders at all hours of preservation at 50C for different incubation periods than that in EYCGG extender. The sperm motility and live sperm dropped (p<0.05) as the incubation period increased from 0 to 8h irrespective of the extender and preservation period. In brief, canine semen extended in TEYCAG extender and preserved for 48h at 50C maintained the semen quality suitable for artificial insemination up to 4h of incubation.